2017
DOI: 10.1111/ene.13450
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis for patients with in‐hospital stroke onset: propensity‐matched analysis from the Safe Implementation of Treatments in Stroke‐East registry

Abstract: Our findings underline the safety and efficacy of IVT for IHS. They also underscore the potential of reducing in-hospital delays for timely tissue plasminogen activator delivery in patients with IHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…'s[ 18 ] study, the most disadvantage is the inclusion of some patients with thrombolysis. As in the previous study,[ 11 ] TT was revealed as the leading risk of HT in AIS patients. The actual correlation between GFR and HT could be confounded by TT due to TT are more strongly responsible for the increased HT risk rather than impaired renal function.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…'s[ 18 ] study, the most disadvantage is the inclusion of some patients with thrombolysis. As in the previous study,[ 11 ] TT was revealed as the leading risk of HT in AIS patients. The actual correlation between GFR and HT could be confounded by TT due to TT are more strongly responsible for the increased HT risk rather than impaired renal function.…”
Section: Discussionsupporting
confidence: 70%
“…[ 9 10 ] The acquisition of HT is more important social concern when interventional management (intravenous or intra-arterial thrombolysis and endovascular therapy) are increasingly used due to which may increase recanalization rate, but at the same time increased the risk of HT. [ 11 ] Therefore, identifying some risk factors predisposing to HT may lead to new preventive strategies. The incidence of kidney dysfunction is higher in stroke patients and, in turn, kidney damage is an important predictor of mortality and all devastating vascular events in patients with AIS.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they found lower thrombolysis rates also caused by significant and often preventable delays: delayed symptom recognition, e.g. due to sedation or less experienced hospital staff[3, 26], less emergency stroke specialist referrals[4, 30, 31], and longer times from stroke onset to imaging or treatment[25, 32]. This combination of higher rates of contraindications to thrombolysis, as well as preventable delays in symptom recognition and diagnosis are plausible explanation for the lower thrombolysis rates found here.…”
Section: Discussionmentioning
confidence: 99%
“…After dichotomization according to the history of dual antiplatelet intake prior to stroke onset, patients in the treatment group (patients with history of dual antiplatelet pretreatment) were matched to control group patients without any prior antiplatelet treatment at stroke onset. For matching, we used a structured, iterative propensity score model with inclusion of all baseline characteristics, except for the history of dual antiplatelet pretreatment, with the primary objective to maximize the balance in the distribution of possible confounders between the 2 aforementioned groups . The corresponding propensity score of the treatment variable (history of dual antiplatelet intake) was calculated for each subject, and a nearest neighbor matching algorithm with a 1:1 allocation was subsequently implemented to match eligible patients in the treatment group (patients with history of dual antiplatelet pretreatment) to patients in the control group (patients without history of antiplatelet pretreatment).…”
Section: Methodsmentioning
confidence: 99%